A House Divided: Grassroots National Religious Perspectives on the Gaza Disengagement and Future of the West Bank. - Tabory, Ephraim; Sasson, Theodore (Journal of Church & State)
This article discusses the religious implications of the Israeli withdrawal from Gaza and the West Bank in 2005. The author discusses the role of Jewish rabbis in the withdrawal process from the Gaza Strip and highlights their divided opinions as to how to react to the withdrawal. The author states that some rabbis encouraged active civil disobedience, while others opted for educational public relations campaigns to address the religious implications of the withdrawal.